EFEKTIVITAS PENGGUNAAN METODE MIN-MIN SOLUTION TERHADAP HASIL BELAJAR SISWA - Eko Prihandono; Ema Dwi Hastuti; Lia Wijaya (Universitas Muhammadiyah Metro, 2024)
Abstract: This research aims to measure the effectiveness of the Min-min Solution method in optimizing student learning outcomes in temperature conversion material. The research was carried out using an experimental approach, through collecting data from Pre-Test and Post-Test questions. Based on analysis of value data using the Paired T Test, a Sig (2-tailed) value of 0.000 was obtained, which means it is smaller than ½ α (0.025). This illustrates a significant change in the Pre-Test and Post-Test scores. These results mean that the Min-min Solution method has a positive influence on improving Post-Test results. Therefore, it is concluded that the application of the Min-min Solution method is effective in optimizing the physics learning outcomes of class IX students at SMP Negeri 2 Bandar Surabaya.